2023
DOI: 10.1002/jmv.28454
|View full text |Cite
|
Sign up to set email alerts
|

Local immune dysregulation and subsequent inflammatory response contribute to pulmonary edema caused by Enterovirus infection in mice

Abstract: Pulmonary edema that comes on suddenly is the leading cause of mortality in handfoot-and-mouth disease (HFMD) patients; however, its pathogenesis is still largely unclear. A range of research suggest immunopathogenesis during the occurrence of pulmonary edema in severe HFMD patients. Herein, to investigate the potential mechanism of immune dysregulation in the development of pulmonary edema upon Enterovirus (EV) infection, we established mouse infection models for Enteroviruses (EVs) including Coxsackievirus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…19 Due to its potential for severe manifestations, including neurological complications and, in rare cases, sudden-onset pulmonary edema leading to fatalities, this disease has gained increased amounts of attention. 20,21 Its prevalence has been on the rise in recent years, leading to greater focus and efforts in disease management. EV-A71 and CV-A16 were the most common viral types associated with HFMD more than 10 years ago, while other enterovirus subtypes became the main subtypes in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Due to its potential for severe manifestations, including neurological complications and, in rare cases, sudden-onset pulmonary edema leading to fatalities, this disease has gained increased amounts of attention. 20,21 Its prevalence has been on the rise in recent years, leading to greater focus and efforts in disease management. EV-A71 and CV-A16 were the most common viral types associated with HFMD more than 10 years ago, while other enterovirus subtypes became the main subtypes in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of HFMD and HA have been reported in various regions worldwide, with an increasing number of cases and associated complications 19 . Due to its potential for severe manifestations, including neurological complications and, in rare cases, sudden‐onset pulmonary edema leading to fatalities, this disease has gained increased amounts of attention 20,21 . Its prevalence has been on the rise in recent years, leading to greater focus and efforts in disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that inflammatory reactions could lead to alterations in pulmonary capillary permeability and severe pulmonary edema [ 7 , 8 ]. Factors such as viral infections and inflammatory cytokines may cause damage to the pulmonary barrier and result in pulmonary edema [ 9 ]. In this case, the patient was diagnosed with infective endocarditis, and despite empirical antibiotic treatment, the infection remained quite severe.…”
Section: Discussionmentioning
confidence: 99%